(untitled) (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Postoperative pain remains a significant problem in patients undergoing abdominal surgeries, and has a profound effect on patient recovery. High-dose opioids hamper bowel motility and increase nausea and vomiting. Intravenous lidocaine has been used as part of a multimodal analgesia protocol for providing effective pain relief and attenuating surgery-associated inflammatory response. Preoperative pregabalin also has a beneficial effect in reducing pain. This study was carried out to assess the efficacy of combining these drugs in reducing pain, paralytic ileus, and stress response. Method: Patients undergoing elective laparotomy were randomized into two groups. Group A patients received preoperative placebo and intraoperative lidocaine infusion. Group B patients received preoperative pregabalin and lidocaine. The pain was assessed using a visual analog scale at 2, 6, 18, and 24 hours postoperatively. Morphine consumption on a patient-controlled analgesia pump was also noted. Surgical stress response was assessed by measuring perioperative total leucocyte count, interleukin-6, and C-reactive protein. Result: Postoperative pain scores at 6, 18, and 24 hours were significantly lower in Group B patients who had received pregabalin. These patients also had lower morphine consumption and earlier bowel recovery as measured by the first passage of stools. Perioperative inflammatory markers were similar in both groups. Conclusion: Preoperative pregabalin when used with intravenous lidocaine has a synergistic effect on reducing postoperative pain and opioid consumption. This also has a beneficial effect on the return of bowel function.